Strategi Manajemen Keuangan Dalam Meningkatkan Profitabilitas Perusahaan Pada PT Saranabaja Perkasa - Aon Haryadi; Adria Wuri Lastari; Mulia Inda Purwati (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2026)
This study aims to determine the financial management strategies implemented and their contribution to increasing the level of company profitability at PT Sarana Baja Perkasa. The method used is qualitative with a descriptive approach. Data sources in this study consist of primary data and secondary data. Primary data was obtained through direct interviews with related parties, namely the financial manager, financial staff, and cashiers at the company's head office. Meanwhile, secondary data was obtained from various internal company documents relevant to the study. Data collection was carried out through interview, observation, and documentation techniques. Meanwhile, data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, with data validity testing using source triangulation and member checking. The results of the study revealed that the financial management strategies implemented include financial planning, cash flow management, cost control, and working capital management that are carried out in a structured manner. The implementation of these strategies has a significant role in increasing company profitability through effective and efficient financial management, thereby driving profit increases, maintaining financial stability, and supporting the company's business sustainability